An integrated microfluidic chip for studying the effects of neurotransmitters on neurospheroids. Issue 6 (8th February 2023) - Mao, Subin; Fonder, Catherine; Rubby, Md Fazlay; Phillips, Gregory J.; Sakaguchi, Donald S.; Que, Long
Abstract : To improve our understanding of how the central nervous system functions, we report the development of an integrated chip for studying the effects of the neurotransmitters on adult rat hippocampal progenitor cell neurospheroids. Abstract : To improve our understanding of how the central nervous system functions in health and disease, we report the development of an integrated chip for studying the effects of the neurotransmitters dopamine and serotonin on adult rat hippocampal progenitor cell (AHPC) neurospheroids. This chip allows dopamine or serotonin located in one chamber to diffuse to AHPC neurospheroids cultured in an adjacent chamber through a built-in diffusion barrier created by an array of intentionally misaligned micropillars. The gaps among the micropillars are filled with porous poly(ethylene glycol) (PEG) gel to tune the permeability of the diffusion barrier. An electrochemical sensor is also integrated within the chamber where the neurospheroids can be cultured, thereby allowing monitoring of the concentrations of dopamine or serotonin. Experiments show that concentrations of the neurotransmitters inside the neurospheroid chamber can be increased over a period of several hours to over 10 days by controlling the compositions of the PEG gel inside the diffusion barrier. The AHPC neurospheroids cultured in the chip remain highly viable following dopamine or serotonin treatment. Cell proliferation and neuronal differentiation have also been observed following treatment, revealing that the AHPC neurospheroids are a valuable in vitro brain model for neurogenesis research. Finally, we show that by tuning the permeability of diffusion barrier, we can block transfer of Escherichia coli cells across the diffusion barrier, while allowing dopamine or serotonin to pass through. These results suggest the feasibility of using the chip to better understand the interactions between microbiota and brain via the gut–brain axis.